Vibration and thermal cycling effects on solder joint reliability - Selvanathen, Daryl (2014)
This report describes vibration and thermal cycling effects on solder joint reliability, especially its relationship concerning the life prediction of solder joints. It highlights critical parameters needed to support a better understanding of solder joint reliability arising from failure mechanisms due to high temperatures, vibration, shock, thermal cycling or a combined variety of them. The literature review includes the necessary foundational knowledge in this subject matter where the estimation of fatigue life, evaluation of random vibration and thermal cycling failures are reviewed. Furthermore, several sample problems were included to aid in understanding.